Computers at risk : safe computing in the information age (National Academy P. WashingtonUS, 1991)
Considers the degree to which a computer system and the information it holds can be protected and preserved. Provides an agenda for public policy; computer and communications security research; technology development; evaluation; and implementation. Focuses on the broad base of deployed computers in the United states; does not emphasize the special problems of government classified information systems.
DC